Realization of Dielectric Sheets for Gain Improvement of Ultra-Wideband Horn Antennas Using 3D Printer Technology - Mehmet A. Belen; Peyman Mahouti (Applied Computational Electromagnetics Society Journal (ACES), 2019)
In this work, 3D printing technology had been used to prototyped 10 dielectric sheets with relative dielectric constant of 2.5 for gain improvement of a TEM horn antenna. By loading the 3D printed dielectric sheets to the aperture of the horn antenna it is achieved to improve the radiation performance of the antenna over an ultra-wide operation band of 2-13 GHz. Here the Periodic dielectric sheets are designed to function similarly to a dielectric lens for focusing the incoming electromagnetic waves to increase directivity properties, while keeping their mismatching characteristics with less size and low manufacturing cost compared to its counterpart lens designs. The dielectric sheets had been prototyped via the use of 3D printing technology for experimental measurements. The measured performance of the proposed 3D printed dielectric loaded TEM horn antenna is compared with its counterpart ultra-wide band gain improvement methods for horn antennas in literature. From the measured results of the prototyped module, not only the proposed 3D printed dielectric sheets are smaller and have lower cost compared to their counterpart designs but also achieves to improve the gain characteristics of the antenna design over an ultra-wide band operation band without a distortion on antenna’s S11 characteristics.